2020
DOI: 10.1007/s11858-020-01128-y
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of mathematics teachers’ competence and their relation to instructional quality

Abstract: Most of the research examining the relation between instructional quality (INQUA) and mathematics teachers' competence was restricted to a limited set of competence facets. Furthermore, mostly variable-oriented approaches were applied that assume homogeneity of teacher competence. In our study, teacher competence is conceptualized as a comprehensive multi-dimensional construct including a broad range of subject-specific and generic facets regarding mathematics teachers' knowledge, skills and beliefs, all asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 62 publications
2
30
0
9
Order By: Relevance
“…For instance, the results of this study underline the need for the promotion of aspects of a more formal nature of the practice of conjecturing (vertical mathematising activities) and of aspects of the practice of proving such as the use of examples that guide the proving process but do not constitute a proof. From our learning approach, it is stated that learning in the processes of professional development aims, through the peripheral participation, to alter the way in-service teachers develop mathematical practices to the way the mathematicians' community of practice develops such practices (Blömeke, Kaiser, König, & Jentsch, 2020;Lave & Wenger, 1991;Podkhodova, Snegurova, Stefanova, Triapitsyna, & Pisareva, 2020;Yilmaz, 2020), always taking into consideration that there are differences between both contexts (Weber, Inglis, & Mejia-Ramos, 2014).…”
Section: Some Reflections On the Resultsmentioning
confidence: 99%
“…For instance, the results of this study underline the need for the promotion of aspects of a more formal nature of the practice of conjecturing (vertical mathematising activities) and of aspects of the practice of proving such as the use of examples that guide the proving process but do not constitute a proof. From our learning approach, it is stated that learning in the processes of professional development aims, through the peripheral participation, to alter the way in-service teachers develop mathematical practices to the way the mathematicians' community of practice develops such practices (Blömeke, Kaiser, König, & Jentsch, 2020;Lave & Wenger, 1991;Podkhodova, Snegurova, Stefanova, Triapitsyna, & Pisareva, 2020;Yilmaz, 2020), always taking into consideration that there are differences between both contexts (Weber, Inglis, & Mejia-Ramos, 2014).…”
Section: Some Reflections On the Resultsmentioning
confidence: 99%
“…En una primera etapa, cada uno de los syllabus fue analizado mediante una codificación cualitativa deductiva (Mayring, 2015), formando categorías a partir de los nuevos paradigmas sobre la formación inicial que ponen el foco en la aproximación al aula escolar y en la resolución de situaciones de aula bajo el marco de la competencia profesional (Ver Figura 1) (Blömeke et al, 2020). En esta línea, la investigación (Blömeke et al, 2020;Grossman et al, 2009;Han et al , 2020) demuestra que la ''formación de la práctica'' es un marco que permite al estudiante de pedagogía experimentar la realidad docente a través de representaciones, descomposiciones y aproximaciones al aula escolar.…”
Section: Etapas Y Propuestas De Análisis Estadísticosunclassified
“…En una primera etapa, cada uno de los syllabus fue analizado mediante una codificación cualitativa deductiva (Mayring, 2015), formando categorías a partir de los nuevos paradigmas sobre la formación inicial que ponen el foco en la aproximación al aula escolar y en la resolución de situaciones de aula bajo el marco de la competencia profesional (Ver Figura 1) (Blömeke et al, 2020). En esta línea, la investigación (Blömeke et al, 2020;Grossman et al, 2009;Han et al , 2020) demuestra que la ''formación de la práctica'' es un marco que permite al estudiante de pedagogía experimentar la realidad docente a través de representaciones, descomposiciones y aproximaciones al aula escolar. Esta aproximación a la realidad escolar, se lleva a cabo en cuatro dimensiones (Blömeke et al, 2020;DeGraff et al, 2015), las cuales son descritas a continuación: Espacio: el proceso de formación debe otorgar la oportunidad al estudiante de pedagogía vivenciar el espacio del aula escolar y todo lo que esto implica, como la interacción y comunicación con niños, niñas y colegas, gestionar el espacio y los recursos de la sala de clase, visualizar la disposición de los recursos, identificar posibles trayectorias de monitoreo, etc.…”
Section: Etapas Y Propuestas De Análisis Estadísticosunclassified
“…In Kuivila's research, teacher competency included leadership and management competency, evidence-based practice competency, subject competency, ethical competency, pedagogical competency, collaboration competency, internationalization competency, and continuous professional development competency (Kuivila et al, 2020). Some scholars believe that the concept of mathematics teachers' competency includes the subject characteristics and common aspects of mathematics teachers' knowledge, skill, and belief (Blömeke et al, 2020). In this study, for entrepreneurial teachers, subject specificity refers to their entrepreneurial competency while the common aspects refer to their teaching competency.…”
Section: Literature Review Research On Competency Theorymentioning
confidence: 99%
“…Further, Wu et al (2018) suggested that information and communication technology can be used to enhance the effectiveness of traditional teaching methods and competency training in EE. An increasing number of scholars are using competency theory to study universities and teachers, for example, using the teacher competency training system to improve competency for education for sustainable development (Weng et al, 2020) and developing a competency-based framework for teachers' entrepreneurial behavior (Van Dam et al, 2010), teachers' entrepreneurial competencies (Peltonen, 2015;Stettiner et al, 2015), the capacity building of teachers of innovation and EE in universities (Trauth et al, 2015), and research on teacher competency and instructional quality (Blömeke et al, 2020).…”
Section: Literature Review Research On Competency Theorymentioning
confidence: 99%